Understanding Chronic Liver Disease in Women: A Clinico-Etiological and Complication-Based Study - M, Dr Isabella Rita; Dr Umashankar; Ramineni, Saketh (Journal of Neonatal Surgery, 2025)
Abstract Background: Chronic liver disease (CLD) in women presents with unique clinical and etiological patterns influenced by biological susceptibility and gender-specific factors. Despite this, focused studies on female patients are limited. Objectives: To analyze the clinical presentation, etiological spectrum, and progression of complications in female patients with CLD over a six-month follow-up period. Methods: This hospital-based cross-sectional observational study was conducted in the Department of General Medicine, Sree Balaji Medical College and Hospital, Chennai. The study began in September 2023 and included 60 female patients aged above 12 years diagnosed with CLD. All patients were evaluated at the time of hospital admission and followed up for a period of six months. Detailed clinical profiles, laboratory investigations, radiological and endoscopic findings, and complications were recorded and analyzed. Results: The mean age of the patients was 44.3 years, with the majority between 31–50 years. Common presenting symptoms included abdominal distension (85%), anorexia (73.3%), and jaundice (56.7%). Cryptogenic cirrhosis (38.3%) emerged as the leading etiology, followed by Hepatitis C (15%) and Hepatitis B (10%). Splenomegaly and loss of body hair were observed in 43.3% of patients. Esophageal varices were present in 36.7% as seen on endoscopy. Elevated AST (70%), ALT (60%), and hypoalbuminemia (43.3%) indicated significant hepatic dysfunction. At six-month follow-up, there was a statistically significant rise in complications such as coagulopathy, spontaneous bacterial peritonitis, sepsis, and hepatorenal syndrome (p<0.05). Conclusion: Female patients with CLD often present with advanced disease and a high burden of complications. Cryptogenic cirrhosis was the most common cause, highlighting the need for in-depth diagnostic evaluation. Early diagnosis and regular follow-up are essential to improve clinical outcomes in this population.